Penerapan Kebijakan Pegawai Pemerintah dengan Perjanjian Kerja (PPPK) terhadap Jabatan Fungsional Keahlian di Mahkamah Konstitusi - Rizka Putri Nareswari; Purwono Sungkowo Raharjo; Fatma Ulfatun Najicha (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to examine the regulatory framework concerning Government Employees with Work Agreements (PPPK), particularly in Functional Expert Positions in Indonesia and to identify how the policy implementation of PPPK in Functional Expert Positions is carried out at the Constitutional Court. The research employs an empirical method with a qualitative approach. The types of data used include both primary and secondary data: primary data was obtained through field interviews, while secondary data consists of documents, information, books, and facts sourced from official records and legislation. The findings of this study indicate that the implementation of policies related to Functional Expert Positions at the Constitutional Court still faces regulatory inconsistencies, especially in the selection mechanism, which does not fully adhere to the established rules. Additionally, competency development for PPPK employees is not supported by systematic planning, which risks creating skill gaps. This situation may lead to uncertainty in career progression and reflects that the management of PPPK still encounters several fundamental challenges in its implementation.